Acceptance Of Artificial Intelligence Technology By UIN North Sumatra Students - Nazmi Hayati; Retno Sayekti (SEAN Institute, 2024)
This research aims to explore the influence of acceptance of artificial intelligence (AI) technology among Muslim students at UIN North Sumatra, as well as to understand their perceptions of the use of AI technology when it is related to religion. The research method used is quantitative analysis with the TAM model. Data was collected through an online questionnaire with 120 respondents. The results show that religious and ethical values ​​significantly influence Muslim students' attitudes towards AI, with concerns about AI's compatibility with Islamic teachings being an important factor. Nonetheless, perceptions of the ease and usefulness of AI in education reflect positive attitudes towards its use. In conclusion, despite challenges related to religious values, Muslim students at UINSU tend to accept AI as a tool in education.